Pengaruh Pengetahuan Kesehatan Gigi Mulut sebagai Faktor Predisposisi Kejadian Karies pada anak usia Sekolah Dasar di UPTD SD Negeri 74 Kabupaten Barru - Sitanaya, Rini; Irayani Yunus, Surya; Lesmana, Hans; Ramdania (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2024)
Dental and oral health problems are one of the major complaints in Indonesia, especially dental caries, which is the most prevalent in both adults and children. The high number of dental caries sufferers is inextricably linked to the lack of knowledge about the causes and prevention of dental caries. Research objectives: This study was conducted to determine the relationship between oral health knowledge and the incidence of dental caries in UPTD SD Negeri 74 Barru. This type of research uses an analytical observational research method with a cross-sectional study approach. It involved 58 samples taken by total sampling from the students of SD Negeri 74 Barru. The results showed that most children in SD Negeri 74 Barru had a fairly good knowledge about dental caries and the incidence of dental caries among students in this school was also in the low category. The results of Chi-square test with a significant value of (0.0067), so it can be concluded that there is a significant relationship between oral health knowledge and the incidence of dental caries.